Synthesis and structural characterization of isothiocyanato-4-methoxypyridine-cobalt(II) complexes with diverse geometries and a bridged 1D coordination polymer showing metamagnetic transition. (1st November 2018) - Mautner, Franz A.; Traber, Magdalena; Fischer, Roland C.; Torvisco, Ana; Reichmann, Klaus; Speed, Saskia; Vicente, Ramon; Massoud, Salah S.
Graphical abstract: Three thiocyanato cobalt(II) complexes with 4-methoxypyridine as co-ligand were synthesized, and were characterized by X-ray structural methods, IR and UV–Vis spectroscopy, magnetic susceptibility and thermogravimetric measurements. Abstract: Three cobalt(II) isothiocyanato complexes with 4-methoxypyridine (4-MOP) as a co-ligand have been synthesized: catena -[Co(4-MOP)2 (μ1, 3 -NCS)2 ] (1 ), trans -[Co(4-MOP)4 (NCS)2 ] (2 ), and [Co(4-MOP)2 (NCS)2 ] (3 ) and structurally characterized by IR, UV–Vis spectroscopy and single crystal X-ray diffraction. The complexes2 and3 are discrete monomeric species with octahedral and tetrahedral geometries, respectively whereas the catena -[Co(4-MOP)2 (μ1, 3 -NCS)2 ] (1 ) is featuring a polymeric 1D system with doubly bridging NCS − groups through the terminals N - and S -donor atoms in a trans octahedral geometry. The thermoanalytical behavior of1 –3 is reported. Magnetic susceptibility of the bridged-isothiocyanato coordination polymer1 was studied down to a temperature of 2 K and at various magnetic dc and ac fields. These measurements indicate a metamagnetic transition in1 .